Doctores hispanos en leyes y cánones por la Universidad de La Sapienza de Roma (1549-1774) - Ramis Barceló, Rafael (Historia de las Universidades, 2017)
The book presents the catalogue of Hispanic doctors in Civil and Canon Law graduated at the University of La Sapienza in Rome from 1549 to 1774. It also includes a list of Portuguese graduates. In La Sapienza, contrary to what has been maintained by many scholars, hundreds of foreign students received their doctorate degrees in Civil and Canon Law. The book, after a presentation of the College of Consistorial Lawyers and the Professors of the Faculty of Civil and Canon Law, emphasizes the international character of the doctoral students and focuses on Spaniards. Decisive contributions can be made going through the list of graduates, supervisors, examiners and witnesses, not only to the identification of Hispanic civilists and canonists, but also to the study of the academic, cultural and political networks, woven in Rome during the Modern Era.--------El libro presenta la nómina de doctores hispanos en leyes y cánones en la Universidad de La Sapienza de Roma desde 1549 hasta 1774. Se incluye asimismo una nómina de graduados portugueses. En La Sapienza, contrariamente a lo que se ha sostenido mayoritariamente, se doctoraron en ambos derechos centenares de estudiantes extranjeros. El libro, tras una presentación del Colegio de Abogados Consistoriales y de los profesores de la Facultad de Leyes y Cánones, enfatiza el carácter internacional de los doctorandos y se centra en los hispanos. A través del elenco de graduados, promotores, examinadores y testigos se puede contribuir decisivamente no sólo a la identificación de legistas y canonistas hispanos, sino también al estudio de las redes académicas, culturales y políticas que se tejieron en Roma durante la época moderna.